The Role of Psychological Well-Being and Work Meaning on Teacher Loyalty in Private Vocational High Schools - Septi Diah Atiningtyas; Barokah Isdaryanti; Joko Sutarto (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study aims to explore the interrelation between teachers’ psychological well-being, work meaning, and loyalty in a private vocational high school in West Java, Indonesia. A descriptive qualitative approach with a phenomenological design was applied. Data were collected through reflective interviews using Google Forms from six permanent teachers with more than five years of teaching experience. The results revealed that teachers’ psychological well-being is developed through gratitude, adaptability, and social support within the workplace. The meaning of work serves as the main source of emotional resilience, as teachers perceive their profession as a personal calling and a form of social–spiritual contribution. Teachers’ loyalty is not determined by financial compensation but rather by psychological comfort and the family-like atmosphere of the school. These findings highlight that psychological well-being and work meaning serve as the core foundations of teachers’ affective loyalty. Therefore, human resource management in education should prioritize psychological well-being as a strategic effort to enhance teachers’ commitment and performance. Keywords: Psychological Well-Being, work meaning, teachers loyalty.